ANALISIS LAYOUT KANTOR PADA PT. GUNUNG SELATAN LESTARI PALEMBANG - Aurantia Marina (Jurnal Ilmiah Ekonomi Global Masa Kini)
The purpose of this study to find and describe the layout of the office at PT. South Mountain Lestari. Methods used are observation and documentation. Based on observations Tata layout at PT. Mount South Lestari Palembang using the short-distance principle to make the movement of employees not loose so that the use of time is not effective. There has been no planning consideration on spatial factors such as lighting, air circulation and illumination, allowing employees not to work as expected by the company. Fresh and clean air will increase the productivity of employees, the lighting there also does not meet the criteria of an office because of its lighting or good lighting is a vital thing that the senses require to perform office tasks. Good lighting will increase work productivity, improve work quality, reduce errors, reduce eye damage, improve employee morale and provide a better image for the company.Keywords: Layout, office and Company